Critical Discourse Analysis On Women Politician During 2024 Election - Riduansyah, Riduansyah; Maella, Nurannafi Farni Syam; Iwan Joko Prasetyo (Jurnal Scientia, 2024)
This study conducts a Critical Discourse Analysis (CDA) on the portrayal of women politicians during the 2024 election, examining how they are represented and the influence of these discourses on their political participation and public perception. Through the literature review, it becomes evident that female politicians frequently encounter gender stereotypes and biases in media and public discourse. Using the CDA methodology, this study examines articles, interviews, and comments from prominent news outlets and social media platforms that discuss women politicians. The findings suggest a tendency to place greater emphasis on women's physical appearance, personality traits, and domestic responsibilities in comparison to men. Discussions of this nature have the potential to undermine the political prowess of women and hinder their participation in the political sphere. The study emphasizes the significance of fostering equitable and impartial conversations on female politicians. It advocates for the media and society to transcend gender stereotypes and promote more political participation of women.